Choice of means of prevention fuel losses from evaporation - Бойченко, С.В.; Черняк, Л.М. (Proceedings of National Aviation University (archive), 2004)
The method of a choice optimum means prevention of fuel losses from evaporation are described in the paper. Distinction of the offered method from known will consist in use of criterion which determination is based on calculation of the cost price of storage of fuel in 1 cubic meter of the storage tank.